Pengembangan Sistem Pemantauan dan Deteksi Serangan pada Ekosistem Rumah Cerdas - Hariyadi, Dedy; Setiawan, Chanief Budi; Setiyadi, Barep (Universitas Muhammadiyah Magelang, 2021)
It is predicted that the growth of smart devices installed in the smart home ecosystem will increase in the future. Smart devices that are connected to each other using wired or wireless networks that have the potential for security holes are attacked by threat actors. Whereas a house is a place that provides comfort for its residents. An attack on the smart home ecosystem allows the operation of the smart home ecosystem to be disrupted or personal information stolen to be used by irresponsible parties. To face the high wave of smart home implementation in the future with potential security holes that always accompany it. This is in accordance with the principle that no system is 100% secure. In this study, attacks on wireless networks can be detected as anomalous traffic. Monitoring and detection in the smart home ecosystem involves supporting components such as sensors, access points, gateway collectors and analysis stacks.